2009
DOI: 10.1089/scd.2008.0017
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Functional Characterization of Human Mesenchymal Stem Cells from Umbilical Cord Blood for Potential Uses in Regenerative Medicine

Abstract: Mesenchymal stem cells (MSCs) represent a promising source of progenitor cells having the potential to repair and to regenerate diseased or damaged skeletal tissues. Bone marrow (BM) has been the first source reported to contain MSCs. However, BM-derived cells are not always acceptable, due to the highly invasive drawing and the decline in MSC number and differentiative capability with increasing age. Human umbilical cord blood (UCB), obtainable by donation with a noninvasive method, has been introduced as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…52 The morphology and differentiation potential of MSCs are dependent upon their source, the culture conditions (supplements, seeding density, number of passages, culture time) and the topographic localization within each colony. 49,53,54 The characteristics of the 3 D scaffolds, such as their chemical composition, topography, and roughness, have been also recognized as significant factors in affecting the cells' behavior. The heterogeneity and morpho-functional variability of MSCs and their microenvironment may explain some of the conflicting data in different research works.…”
Section: Discussionmentioning
confidence: 99%
“…52 The morphology and differentiation potential of MSCs are dependent upon their source, the culture conditions (supplements, seeding density, number of passages, culture time) and the topographic localization within each colony. 49,53,54 The characteristics of the 3 D scaffolds, such as their chemical composition, topography, and roughness, have been also recognized as significant factors in affecting the cells' behavior. The heterogeneity and morpho-functional variability of MSCs and their microenvironment may explain some of the conflicting data in different research works.…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear cells derived from human umbilical cord blood and obtained by a negative immunoselection technique exhibited either osteoclast-like or mesenchymal-like phenotypes [47] . However, these cells were able to produce homogeneous populations of MSCs displaying a fibroblast-like morphology while expressing mesenchyme-related antigens and showing differentiation capability for osteoblastic and early chondroblastic lineages.…”
Section: Therapeutic Application Of Umbilical Cord Mscs For Joint Patmentioning
confidence: 99%
“…However, these cells were able to produce homogeneous populations of MSCs displaying a fibroblast-like morphology while expressing mesenchyme-related antigens and showing differentiation capability for osteoblastic and early chondroblastic lineages. This study by Barachini et al [47] is one of the few investigating human umbilical cord blood-derived MSC growth and differentiation on three-dimensional scaffolds. The potential applications in regenerative medicine and tissue engineering of umbilical cord blood-derived MSCs were illustrated by their ability to grow on biodegradable microfiber meshes and their capability to differentiate into mature osteoblasts when cultured inside human plasma clots; this suggests their potential applications in orthopedic surgery.…”
Section: Therapeutic Application Of Umbilical Cord Mscs For Joint Patmentioning
confidence: 99%
“…Umbilical cord blood also has a low contaminate rate of malignant cells and low immunogenicity [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have demonstrated that mesenchymal stem cells (MSCs), the precursor cells of stromal cells [6][7][8], also exist in hUCB [2,[9][10][11][12][13][14]. Human umbilical cord blood-derived mesenchymal stem cells (hUCBDMSCs) obtained from colony-forming unit fibroblasts (CFU-F) display a homogeneous morphology and express some CD molecules that are characteristic of bone marrow-derived MSCs [12].…”
Section: Introductionmentioning
confidence: 99%